Modular construction system in Malaysia : issues for research in sustaining an affordable home project / Salmiah Aziz and Mohd Rofdzi Abdullah - Salmiah, Aziz; Mohd Rofdzi, Abdullah (2015)
A house that is manufactured in factory processes and produced in a module (as a unit) is defined as Modular Construction System (MCS). It was also known as Modern Method of Construction (MMC) or Offsite Fabrication (OSF) in the construction industry in other developed countries. In Malaysia, the MCS or Volumetric Modules building was categorised as an innovative method in Industrialised Building Systems (IBS) classification. It was considered to promote a solution to the construction industry in enhancing a better productivity and quality objectives. Hence, it seemed to achieve and satisfied the sustainable issues of the housing industry. From the previous research findings such as availability of reliable manufacturers, sustained and durable materials, accessibility to site, factory location, best transportation routes and management, user perception, authority approval, manufacturing and production cost are the outstanding issues that challenged the adoption of modular construction system in Malaysia. This paper is a division of current research on modular design for an affordable home. The adoption of a new method (MCS) was anticipated to promote a new paradigm and way forward for IBS industry to solve its current problems that it has to face in the construction industry. It was expected that the adoption of modular construction into IBS was the avant-garde to produce more affordable home in future. The data and information presented in this paper was gathered from the reviews of the available relevant literature related to MCS and IBS in Malaysia. This paper suggested an analysis of the initial findings for MCS issues to be searched and explored in depth in Malaysia context. This paper also recommended a conclusion that green and sustainability agenda in affordable housing construction are underpinned by design ―combinatorial concept‖ of MCS.